Association between Vitamin Intake and Chronic Kidney Disease According to a Variant Located Upstream of the PTGS1 Gene: A Cross-Sectional Analysis of Shika Study - Pham, Kim-Oanh; Hara, Akinori; Tsujiguchi, Hiromasa; Suzuki, Keita; Suzuki, Fumihiko; Miyagi, Sakae; Kannon, Takayuki; Sato, Takehiro; Hosomichi, Kazuyoshi; Tsuboi, Hirohito; Nguyen, Thao Thi Thu; Shimizu, Yukari; et al. (Nutrients, 2022)
Chronic kidney disease (CKD) patients have been advised to take vitamins; however, the effects have been controversial. The individual differences in developing CKD might involve genetic variants of inflammation, including variant rs883484 located upstream of the prostaglandin-endoperoxide synthase 1 (PTGS1) gene. We aimed to identify whether the 12 dietary vitamin intake interacts with genotypes of the rs883484 on developing CKD. The population-based, cross-sectional study had 684 Japanese participants (≥40 years old). The study used a validated, brief, self-administered diet history questionnaire to estimate the intake of the dietary vitamins. CKD was defined as estimated glomerular filtration < 60 mL/min/1.73 m2. The study participants had an average age of 62.1 ± 10.8 years with 15.4% minor homozygotes of rs883484, and 114 subjects had CKD. In the fully adjusted model, the higher intake of vitamins, namely niacin (odds ratio (OR) = 0.74, 95% confidence interval (CI): 0.57–0.96, p = 0.024), α-tocopherol (OR = 0.49, 95% CI: 0.26–0.95, p = 0.034), and vitamin C (OR = 0.97, 95% CI: 0.95–1.00, p = 0.037), was independently associated with lower CKD tendency in the minor homozygotes of rs883484. The results suggested the importance of dietary vitamin intake in the prevention of CKD in middle-aged to older-aged Japanese with minor homozygous of rs883484 gene variant.